Tourism transformations in protected area gateway communities - Slocum, Susan L.; Wiltshier, Peter; Read, John B. IV (Wallingford, Oxfordshire Boston, MA CABI, 2022)
"Gateway communities are those located adjacent to protected areas and are often the communities most impacted by tourism visitation and are dependent on tourism revenue. This book presents informed, interpreted, and nuanced approaches towards protect area management and conservation, based on bottom-up local experiences by the gateway communities"--
Introduction / Peter Wiltshier and John B. Read IV -- Appalachian Trail communities : gateway partners in parks and protected area management / Robert S. Bristow, Julie Judkins, and Jessica Schottanes -- Building a gateway to the Arctic : a political economy perspective on tourism development and conservation in Finnish Lapland / Dorothee Bohn and C. Michael Hall -- Gateway community relationships with a U.S. national park : a qualitative exploration of community member, concessioner, and Grand Teton National Park staff perspectives / N. Qwynne Lackey, Kelly S. Bricker, and Russell M. Hicks -- Advocacy for protected areas in the Caribbean : a collaborated approach to ecotourism in Antigua and Barbuda / Therez B. Walker and Natalya Lawrence -- Contribution of tourism to sustainable development : Samalayuca Dunes (Mexico) / Manuel Ramón González-Herrera, Rosa Herminia Suárez-Chaparro, and Karina Hernández-Casimiro.
Includes bibliographical references and index.
Keywords: Ecotourism; Protected areas -- Public use; Tourism -- Environmental aspects